Ukuran Perusahaan, Profitabilitas, Likuiditas dan Pengungkapan Tanggungjawab Sosial - Antari, Ni Nyoman Desi; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 30 No 11 (2020), 2020)
This research was conducted to obtain empirical evidence about the influence of company size, profitability, and liquidity on the Corporate Social Responsibility Disclosure of high profile companies that listed on the Indonesian Stock Exchange in 2015-2018. The results of this research indicate that CSR Disclosure eis influenced by company size, but not influenced by profitability and liquidity. This research has practical policy implications for companies, where the policies of the company must provide balanced attention to all components directly or indirectly involved in the course of the company's business activities. The implications of further research can be used as a reference in making investment-related decisions. Keywords: CSR Disclosure; Company Size; Profitability; Liquidity; High Profile.